Task Scheduling in Cloud Computing Environment - Rajak, Nidhi; Shukla, Diwakar (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the recent area of research where many applications are used. It provides virtual resources and It is based on parallel computing, distributed computing and grid computing which is the extension of previous computing. In this paper, we have introduced the fundamental of cloud computing, brief introduction of task scheduling in cloud environment and its classification of task scheduling such as heuristic, energy efficient and hybrid scheduling. Discussed some performance metrics such as make span, resource cost scalability, reliability and resource utilization. Task scheduling is play very important role in the cloud environment because it’s provide efficient utilization of resources and also provide the user requirements. The major objective of any task scheduling problem is to minimize overall execution time and reduces the cost.